Adsorption of fish lipids on sludge particles - Dacuyan, Rebecca R. (1998)
A major problem encountered in anaerobic digestion of waste is the adsorption of fatty solids on sludge which causes a decrease in the rate of anaerobic reactions and sludge wash-out due to flotation Adsorption of lipids on sludge and other surfaces adversely affect the treatment process. So far, there is hardly any study on the effect of different factors that could influence adsorption of fish lipids and proteins on sludge particles. In this study, the effects of pH, temperature and type of adsorbent on fish lipid adsorption was determined. Instead of actual fish processing wastewater, fish slurry prepared using indian oil sardine (Sardinella longiceps) was used in the experiment. In batch experiments, fish wastewater was stirred for 20 minutes at given pH and temperature conditions and decanted to determine its effect. Lipids in the sludge were determined. the pH maxima for fish lipid adsorption on anaerobic sludge at 30 deg.C were found to be between 4 and 6. In the pH range 4-9, the adsorbed liquids on glass beads is independent of pH. The amount of lipids adsorbed in the sludge has a minima at temperature between 25 and 40 deg.C. In the temperature range 20-50 deg.C, the adsorbed lipids on glass beads is independent of temperature.
Computer print-out.
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Adsorption (Biology); Lipids; Sewage sludge; Sewage